2017
DOI: 10.1111/jdv.14376
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sun‐protective behaviour and intentional sun tanning in German adolescents and adults: results of a nationwide telephone survey

Abstract: As individual sun-protective measures are easy to implement and provide effective protection against high-risk UV exposure, campaigns on skin cancer prevention in Germany should put a stronger focus on young adults, men, less educated individuals and those with immigration background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
51
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 44 publications
11
51
3
3
Order By: Relevance
“…These findings are in line with international studies demonstrating the important influence of self-perceived attractiveness on self-esteem in adolescence [46,47]. Furthermore, enhancing one's attractiveness is a primary motivation for tanning in adolescents both in Brazil and worldwide [43,48,49]. In addition, the success of appearance-based photoaging intervention mobile apps, in which an image is altered to predict future appearance in the fields of tobacco and adiposity prevention, shows promise for these interventions in behavioral change settings [50][51][52][53][54][55].…”
Section: Current Knowledge On School-based Skin Cancer Preventionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are in line with international studies demonstrating the important influence of self-perceived attractiveness on self-esteem in adolescence [46,47]. Furthermore, enhancing one's attractiveness is a primary motivation for tanning in adolescents both in Brazil and worldwide [43,48,49]. In addition, the success of appearance-based photoaging intervention mobile apps, in which an image is altered to predict future appearance in the fields of tobacco and adiposity prevention, shows promise for these interventions in behavioral change settings [50][51][52][53][54][55].…”
Section: Current Knowledge On School-based Skin Cancer Preventionsupporting
confidence: 89%
“…Unhealthy behavior with respect to UV exposure is mostly initiated in early adolescence [42], commonly with the belief that a tan increases attractiveness [43][44][45] and the problems related to melanoma as well as skin atrophy are too far in the future to fathom.…”
Section: Current Knowledge On School-based Skin Cancer Preventionmentioning
confidence: 99%
“…In an earlier publication by our study group, similar associations were shown for the adoption of sun-protective measures, i.e. measures recommended for the primary prevention of skin cancer [22]. …”
Section: Discussionmentioning
confidence: 53%
“…Our study adds that persons with an immigrant background (a population group that is central in the current debate on health inequality in Germany [21]) showed a lower participation rate. Since earlier research by our working group showed that they are also more likely to show high-risk sun exposure behavior [22] - a major risk factor for skin cancer - there is a critical need for strategies aiming to increase SCS participation rates among these groups. …”
Section: Discussionmentioning
confidence: 99%
“…Female students in our study proved to be more prone to using a sunbed than male – not only they use it more often, but also they plan to use them more frequently in the future. The female aspiration to intentional tanning in order to enhance attractiveness has been described in recent literature across Europe . Also, younger students consider the sunbeds not to be so harmful and tend to start with the sunbeds at a younger age, a phenomenon already registered in different countries …”
Section: Discussionmentioning
confidence: 88%